Makna Digital Activism bagi Generasi Z di Paroki Maria Ratu Semesta Alam Sungai Durian dalam Tinjauan Interaksionisme Simbolik Herbert Blumer - Vinsensius Mischa Aldeo; Gregorius Agung (Sekolah Tinggi Widya Sasana, 2025)
This study focuses on the meaning of digital activism (DA) for Generation Z in the Parish of Maria Ratu Semesta Alam Sungai Durian, employing Herbert Blumer’s symbolic interactionism as the theoretical framework. Digital activism is a form of socio-political engagement that uses digital technology to organize, advocate, and voice change. DA is not merely a technical activity, but rather a symbolic act that reflects identity, solidarity, and moral responsibility. The research adopts a qualitative method through in-depth interviews with five Gen Z informants who are active on social media and have participated in DA campaigns. Analysis was conducted by positioning meaning as a social construct shaped and continuously renewed through interaction. Findings reveal that DA is understood in diverse ways: as a symbol of struggle and social concern, as a means of solidarity, and as a form of emotional expression. These meanings are constructed through interactions with peers, communities, and public discourse in digital platforms. DA thus functions as a symbolic arena where identity and Prosiding Seri Filsafat Teologi, Vol. 35 No. 34 518 solidarity are negotiated, while also remaining ambivalent, as it can foster critical awareness but also risk devolving into shallow participation. The study suggests that the parish should provide digital literacy guidance and encourage the linkage between digital activism and real-life actions. Further research is recommended to expand the respondent base and explore the relationship between DA and offline social engagement.